Effect of stereotactic radiotherapy on immune microenvironment of lung cancer - Xiao, Yao; Zhuang, Hongqing (Frontiers in Immunology, 2022)
Stereotactic radiotherapy (SRT) is one of the main treatment modalities for lung cancer, and the current SRT approach combined with immunotherapy has initially presented good clinical efficacy in lung cancer. SRT activates the immune system through in situ immunization, releasing antigens into the blood, which promotes the antigen–antibody response and then induces tumor cell apoptosis. Dose fractionation has different effects on the immune microenvironment, and the tumor microenvironment after SRT also changes over time, all of which have an impact on SRT combined immunotherapy. Although much research on the immune microenvironment of SRT has been conducted, many problems still require further exploration.